Wives’ backgrounds, perception towards family values and physical aggression - Edalati, Ali; Redzuan, Ma’rof; Mansor, Mariani; Abu Talib, Mansor (EuroJournals Publishing, 2009)
The focus of this paper is on the relationship between backgrounds, perceptions towards family values and physical aggression among Iranian wives. The paper is based on a study carried out among 337 wives who suffered physical aggression. Physical aggression was measured using Straus Questionnaire of Conflict Tactic Scale (CTS). There was a significant relationship between duration of marriage, women age, and number of children with family values. There was no relationship between family income and women education with family values. An Independent Sample t-test was utilized to investigate the differences across the two means of groups. As the result, a significant difference was found between women employment and family values where t = 4.48, p ≤.01. An Independent Sample t-test was utilized in order to test the means of the two performances. It was found that there is no significant difference between husband employment and family values. There was no significant difference between the experiences of violence before marriage in terms of the perception towards family values. There was also no significant relationship between family values and female physical aggression.